Subjective well-being and air quality in Germany - Maike Schmitt (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
This paper analyses the relation between air quality and subjective well-being in Germany. Life Satisfaction (LS) data from the German Socio-Economic Panel Study (SOEP) is connected with daily county pollution in terms of carbon monoxide (CO), nitrogen dioxide (NO2) and ozone (O3) from 1998 to 2008. The assumed microeconometric happiness function is estimated considering individual time invariant effects. It is observed that O3 has a significant negative impact on life satisfaction. The estimated influence of current CO as well as NO2 is not significant. Moreover, I found that LS of people with environmental worries is more affected by ozone pollution. This was not the case for people with a bad health status. Using the marginal rate of substitution between income and air pollution, it is calculated that an increase of one µg/m3 (1 Mikrogramm/m3) in daily average county O3 has to be compensated by an increase of exteuro11.33 in monthly net household income to hold an average individual's LS constant.
Keywords: 330; life satisfaction; air pollution; environmental quality